Analisis Kebutuhan Pegembangan Perangkat Pembelajaran Tematik Berbasis Permainan Sumputan Untuk Mengembangkan Pengetahuan Kesiapsiagaan Bencana Gempa Bumi Siswa Sekolah Dasar - Arief Agrian; Hasnawati Hasnawati; Dwi Anggraini (JURIDIKDAS, 2022)
This research aims to analyze the needs of development thematic learning device based on sumputan game for earthquake awareness and preparedness in elementary state school in Bengkulu city.  This research is a form of research and development (R&D) using ADDIE model, which involves analysis,design,development,implementation and evaluation. The needs of analysis in this research has been done based on student needs, characterized analysis and also curriculum analysis. For the result from this research taken from used analysis were “daerah tempat tinggalku” (my hometown) the sub-theme development “kehidupan alam disekitar tempat tinggalku ( the natural resources in my hometown) the indicators development and the development of learning purposes. The result of needs analysis shows that thematic learning device based on sumputan game for earthquake awareness and preparedness could be expanded.Keywords: Analyze, Development, Learning device,  Sumputan, Earthquake.